Sociodemographic and clinical profile of patients with Multiple Myeloma treated in Passo Fundo, Rio Grande do Sul (Research, Society and Development, 2024)
Introduction: Multiple Myeloma (MM) is a malignant neoplasm related to the bone marrow. It affects several sites, producing varied and non-specific symptoms that make diagnosis difficult. Most patients are over 60 years old and consequently have comorbidities. Treatment protocols are evolving, but the drugs used still have toxic potential, causing significant adverse effects. The objective was to analyze the sociodemographic and clinical profile of patients diagnosed with MM and the main adverse effects observed after starting treatment. Methodology: A cross-sectional, descriptive, and observational study was carried out with patients with MM treated at a Passo Fundo hospital (RS). Interviews were conducted using a questionnaire and electronic medical records were analyzed. Results: there was a predominance of males, with a median age of 60.4 years and white color. Systemic arterial hypertension and cardiovascular diseases were the predominant comorbidities. The effects of the chemotherapy drugs can compromise quality of life and lead to poor patient compliance, so it is important to know the profile and individualize each therapy. The most used treatment protocol was Bortezomib+Cyclophosphamide+Dexamethasone (VCD). The most common side effects were loss of appetite, weight loss, headache, and neuropathy. Conclusion: This is an increasingly prevalent disease due to the aging population. Knowing more about patients' profiles can facilitate diagnosis, speed up neoplastic control, and allow for better allocation of public health resources.